2015
DOI: 10.2340/00015555-2080
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma Inhibits Melanogenesis and Induces Apoptosis in Melanocytes: A Pivotal Role of CD8+ Cytotoxic T Lymphocytes in Vitiligo

Abstract: Increased expression of the cytokine interferon (IFN)-γ plays a pivotal role in vitiligo-induced depigmentation. However, the major source of IFN-γ in vitiligo patients and the mechanisms underlying melanocyte destruction are unknown. In this study, a large number of skin infiltrating IFN-γ+ cells and CD8+ T cells were detected in progressive vitiligo. Among the peripheral blood mononuclear cells (PBMCs) of vitiligo patients, CD8+ cytotoxic T lymphocytes (CTLs) that express IFN-γ exhibited significant expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
119
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 41 publications
11
119
0
9
Order By: Relevance
“…Immunohistochemical studies showed infiltration of Th17 cells in vitiligo skin samples [58], and both serum and lesional expression of IL17 are increased in vitiligo [21]. That IFN-c inhibiting melanogenesis and inducing apoptosis in melanocytes reveals a pivotal role of CD8 + cytotoxic T lymphocytes in vitiligo [59]. Cytokines such as IL-1b, IL-17, IFN-c and other melanocyte growth factors (bFGF and ET-1) could be considered as promising targets to vitiligo treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemical studies showed infiltration of Th17 cells in vitiligo skin samples [58], and both serum and lesional expression of IL17 are increased in vitiligo [21]. That IFN-c inhibiting melanogenesis and inducing apoptosis in melanocytes reveals a pivotal role of CD8 + cytotoxic T lymphocytes in vitiligo [59]. Cytokines such as IL-1b, IL-17, IFN-c and other melanocyte growth factors (bFGF and ET-1) could be considered as promising targets to vitiligo treatment.…”
Section: Discussionmentioning
confidence: 97%
“…[21] In addition, Yang et al . showed that IFN-g inhibits melanogenesis in primary cultured human melanocytes by altering melanogenic enzyme messenger RNA expression in addition to increased melanocyte apoptosis via direct affect of IFN-g.[22]…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies against tyrosine hydroxylase and various pigment cell-surface antigens that are specific to melanocytes have been identified in the sera of vitiligo patients [42,43]. Additionally, studies have supported a melanocyte-specific immune reaction driven by cytotoxic CD8+ T cells[44,45]. Lastly, Th1, Th2, and more recently Th17 type cytokines have been significantly quantified in the sera and skin of patients with vitiligo[46,47].…”
Section: Vitiligomentioning
confidence: 99%